The eye in cerebral malaria: what can it teach us? - Maude, R; Dondorp, A; Abu Sayeed, A; Day, N; White, N; Beare, N (2009)
The pathophysiology of coma in cerebral malaria (CM) is not well understood. Obstruction of microcirculatory flow is thought to play a central role, but other hypotheses include roles for parasite- and host-derived factors such as immune mediators, and for increased blood-brain barrier permeability leading to raised intracranial pressure. The retinal vasculature is a direct extension of the cerebral vasculature. It is the only vascular bed easily accessible for visualisation and provides a unique opportunity to observe vascular pathology and its effect on neurological tissue. A specific retinopathy has been well described in African children with CM and its severity correlates with outcome. This retinopathy has been less well described in adults. The central mechanism causing malarial retinopathy appears to be microvascular obstruction, which has been demonstrated in affected retinas by fluorescein angiography. The presence in a central nervous system tissue of microvascular obstruction strongly supports the hypothesis that the sequestration of erythrocytes in small blood vessels and consequent obstruction of microcirculatory flow is an important mechanism causing coma and death in CM. Despite advances in the antimalarial treatment of severe malaria, its mortality remains approximately 15-20%. Adjunctive treatment targeting sequestration is a promising strategy to further lower mortality.